Properties of hantavirus infection model / Norhuda Mohammed, Asyura Abd Nassir and Nazirah Ramli - Mohammed, Norhuda; Abd Nassir, Asyura; Ramli, Nazirah (2012)
Hantavirus is a group of viruses that can cause Hantavirus Pulmonary Syndrome (HPS) and Hemorrhagic Fever with Renal Syndrome (HFRS). Human contract this virus through their rodent hosts. Since the discovery of Hantavirus, there is still no vaccination for the diseases caused by the viruses. This situation has inspired researchers to explore the ecology and epidemiology of Hantaviruses in 'order to come out with a better solution in preventing this infection. In this paper, we investigate the mathematical model of Hantavirus infection known as Abramson-Kenkre (AK) model. The result shows that by changing the values of certain data such as the transmission rate responsible for infection, the birth rate and the natural death rate, different results can be obtained.